2017
DOI: 10.3390/brainsci7110140
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injury in Autism Spectrum Disorder and Intellectual Disability: Exploring the Role of Reactivity to Pain and Sensory Input

Abstract: This paper provides information about the prevalence and topography of self-injurious behavior in children and adults with autism spectrum disorder and intellectual disability. Dominant models regarding the etiology of self-injury in this population are reviewed, with a focus on the role of reactivity to pain and sensory input. Neuroimaging studies are presented and suggestions are offered for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 85 publications
0
46
1
7
Order By: Relevance
“…Murray et al [] also observed higher psychotropic treatment rates in females with ASD in the UK. A multitude of other gender related, but unmeasured symptoms, such as functional social behavior, aggression or self‐injurious tendencies might also play a role in the choice of whether to initiate psychotropic treatment or not [Bresin & Schoenleber, ; Halladay et al, ; Summers et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Murray et al [] also observed higher psychotropic treatment rates in females with ASD in the UK. A multitude of other gender related, but unmeasured symptoms, such as functional social behavior, aggression or self‐injurious tendencies might also play a role in the choice of whether to initiate psychotropic treatment or not [Bresin & Schoenleber, ; Halladay et al, ; Summers et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the factors that influence the presence and severity of self-injury within autism must be integrated with evidence-based models of the function and psychological mechanisms underpinning self-injury. For individuals with an intellectual disability, many of whom have co-morbid autism, the most influential and evidence-based explanatory model of self-injurious behaviour is derived from operant learning theory through an application of applied behaviour analysis (Summers et al 2017 ). Within this model, self-injury is understood to occur as a result of positive or negative reinforcement and can be mediated by contingencies in the individual’s social, sensory and material environment.…”
Section: Introductionmentioning
confidence: 99%
“…These rhythmic and repetitive SIB are evaluated in studies of populations with both autism and intellectual disability (ID)/impaired adaptive functioning (Richards et al 2012 , 2016 ; Summers et al 2017 ; Baghdadli et al 2003 ; Weiss 2002 ). In these samples, SIB has predominantly been conceptualised within an operant learning framework (Summers et al 2017 ) as a response acquired and maintained through reinforcement and mediated by sensory and environmental contingencies. Yates ( 2004 ) proposed these “stereotyped SIB” displayed by autistic/ID samples differ categorically from “impulsive” self-harm displayed by neurotypical samples; however this theory was derived from a developmental psychopathology framework rather than empirical data and as such warrants further investigation.…”
mentioning
confidence: 99%